Cortical Thinning and Ventricle Enlargement in Neuromyelitis Optica Spectrum Disorders - Tian, De-Cai; Xiu, Yuwen; Wang, Xinli; Shi, Kaibin; Fan, Moli; Li, Ting; Li, Huining; Su, Lei; Ma, Yuetao; Xu, Wangshu; Song, Tian; Liu, Yaou; et al. (Frontiers in Neurology, 2020)
BACKGROUND: In neuromyelitis optica spectrum disorders (NMOSD) inﬂammation is not the sole driver of accumulation of disability, neurodegeneration is another important pathological process. We aim to explore different patterns of cortical atrophy and ventricular enlargement in NMOSD. METHODS: We retrospectively analyzed a cohort of 230 subjects, comprising of 55 healthy controls (HCs), 85 MS and 90 NMOSD patients from Tianjin Medical University General Hospital and Beijing Tiantan Hospital. Different compartments of the brain (total grey, cortex, subcortex grey, and ventricle volume) were evaluated with the Freesurfer. Multiple linear regressions were adopted to explore associations between cortex volume and predict factors. RESULTS: Compared to HCs, NMOSD and MS displayed an enlarged lateral and 3rd ventricle (p<0.001), whilst expansion of the 4th ventricle was observed in MS rather than NMOSD (p=0.321). MS and NMOSD patients exhibited cortical thinning in comparison with HCs. However, pronounced cortical atrophy were only signiﬁcant in precuneus, parahippocampal and lateral occipital lobe between MS and NMOSD. Patients with NMOSD had decreased local gyrification index in orbitofrontal and precuneus lobe, and reduced pial surface area. Linear regression analysis revealed cortex volume were predicated by advanced age (standardized β=-0.404, p=0.001) as well as prolonged disease history (standardized β=-0.311, p=0.006). CONCLUSION: NMOSD exhibited global cortex atrophy with enlarged lateral and 3rd ventricle. Moreover, cortex volume is associated with age and disease duration.